An Investigation into Customers Returns Practices: A Survey in Nottingham - Madzlan, Noor Al Iman (2008)
Literature asserts that product acquisition is the key to a profitable reverse supply chain. Interestingly, liberal return policies have been blamed for the surge of returns and variability in the products acquired from the market. Whilst there is some research that deals with return policies amongst the supply chain players, there is limited behavioural study on the initiator of returns ÃÂ¢ÃÂÃÂ the consumers. This study attempts to find consumer trends, behavioural patterns and perceptions pertaining to product returns. An original 5-page questionnaire was designed to capture the different behavioural patterns and perceptions across different shopping environments and product categories. Also the questionnaire contained questions relating to past experiences and reactions. Elements of rationality, fairness, ethics and satisfaction were also probed in the questionnaire. The survey was conducted within Nottingham with a total of 214 responses. Amongst many interesting findings, the survey discovered that the frequency of returns is not linked to demographics but has a strong link to awareness of return policies. Also, those who were ethical tend to return fewer products. All in all, most consumers are satisfied with current practices of return policies and are generally rational in their expectations of a fair returns policy.